Sharing data to better understand one of the world’s most significant shared experiences: data resource profile of the longitudinal COVID-19 psychological research consortium (C19PRC) study - McBride, Orla; Butter, Sarah; Hartman, Todd; Murphy, Jamie; Hyland, Philip; Shevlin, Mark; Gibson-Miller, Jilly; Levita, Liat; Mason, Liam; Martinez, Anton; McKay, Ryan; Lloyd, Alex; et al. (International Journal of Population Data Science, 2022)
This paper serves to alert IJPDS readers to the availability of a major new longitudinal survey data resource, the COVID-19 Psychological Research Consortium (C19PRC) Study, which is being released for secondary use via the Open Science Framework. The C19PRC Study is a rich and detailed dataset that provides a convenient and valuable foundation from which to study the social, political, and health status of European adults during an unprecedented time of change as a direct result of the COVID-19 pandemic and Brexit. Here, we provide an overview of the C19PRC Study design, with the purpose of stimulating interest about the study among social scientists and maximising use of this resource.